Predictive Value of Diffusion, Glucose Metabolism Parameters of PET/MR in Patients With Head and Neck Squamous Cell Carcinoma Treated With Chemoradiotherapy - Kedves, András; Tóth, Zoltán; Emri, Miklós; Fábián, Krisztián; Sipos, Dávid; Freihat, Omar; Tollár, József; Cselik, Zsolt; Lakosi, Ferenc; Bajzik, Gábor; Repa, Imre; Kovács, Árpád (Frontiers in Oncology, 2020)
Purpose: This study aims to evaluate the predictive value of the pretreatment, metabolic, and diffusion parameters of a primary tumor assessed with PET/MR on patient clinical outcomes. Methods: Retrospective evaluation was performed using PET/MR image datasets acquired using the single tracer injection dual imaging of 68 histologically proven head and neck cancer patients 4 weeks before receiving definitive chemoradiotherapy (CRT). PET/MR was performed before the CRT and 12 weeks after the CRT for response evaluation. Image data (PET and MRI-diffusion weighted imaging [DWI]) was used to specify the maximum standard uptake value, the peak lean body mass corrected, SUVmax, the metabolic tumor volume, the total lesion glycolysis (SUVmax, SULpeak, MTV and TLG), and the mean apparent diffusion coefficient (ADCmean) of the primary tumor. Based on the results of the therapeutic response evaluation, two patient subgroups were created—one with a viable tumor, and another without. Metabolic and diffusion data, from the pretreatment PET/MR and the therapeutic response, were correlated using Spearman’s correlation coefficient and Wilcoxon’s test. Results: After completing the CRT, a viable residual tumor was detected in 36/68 (53%) cases, while 32/68 (47%) patients showed complete remission. However, no significant correlation was found between the pretreatment parameter, ADCmean (p = 0.88), and the therapeutic success. The PET parameters, SUVmax and SULpeak, MTV, and TLG (p = 0.032, p = 0.01, p < 0.0001, p = 0.0004) were statistically significantly different between the two patient subgroups. Conclusion: This study found that MRI-based (ADCmean) data from FDG PET/MR pretreatment could not be used to predict therapeutic response, while the PET parameters SUVmax, SULpeak, MTV, and TLG, proved to be more useful; thus their inclusion in risk stratification may also be of additional value.